MLA 10-95 - Pilot Inventory Of Inactive And Abandoned Mine Lands, East Fork Pine Creek Watershed, Shoshone County, Idaho - Sam McNary (The National Institute for Occupational Safety and Health (NIOSH), 1995)
The U.S. Bureau of Mines used the East Fork Pine Creek watershed to conduct a pilot study for an inactive and abandoned mine lands inventory, during which techniques and methodologies would be developed for subsequent inventories. A total of 177 waste dump samples, 191 mill tailings samples, and 36 stream sediment samples were collected. Water samples were collected from 18 sample sites during five sampling events. Waste dump, tailings, and stream sediment samples were analyzed for antimony, arsenic, cadmium, copper, iron, lead, mercury, and zinc. Results indicate a multidisciplinary approach is necessary: disciplines should include geology, geostatistis, geochemistry, geophysics, biology, hydrology, and remote sensing; small prospects do not generally contribute to watershed contamination, major mine and mill sites may contribute metal enriched sediment of metal enriched water; speciation studies and bioavailability studies are important.